Sternal interferential current stimulation after sternotomy: A randomized, sham-controlled trial on pain and wound healing - Nils Schulz; Gian Vo; Pascal van Wijnen; Tim Wilhelmi; Michael Coch; Uwe Lange; Philipp Klemm (Journal of Rehabilitation Medicine)
Objective: To evaluate the effect and safety of serial interferential current stimulation on postoperative pain and wound healing after sternotomy in cardiac rehabilitation.